Analysis of Campaign Materials for Billboards of Regent Candidates to Increase Electability in the 2024 Banggai Regency Election - Falimu, Falimu; Batjo, Ririn; Zaman, Wildan (PT. Anagata Sembagi Education, 2025)
The 2024 regional elections (Pilkada) have their own unique characteristics, one of which is the emergence of young figures who have directly entered the world of politics. One of the campaign media used is billboards, which are spread across various cities in Indonesia. Billboards are outdoor media commonly used by presidential and legislative candidates to convey campaign messages. Generally, campaigns are conducted thematically and tailored to specific objectives. By starting the campaign early, candidates hope to attract sympathy and gain support from the public. The purpose of this study is to determine the semiotic meaning of photos in Giring's campaign billboards as a candidate for President in 2024. The focus of this research is how the visual meaning in the billboards is analyzed using Roland Barthes' semiotic approach with a qualitative descriptive method. In general, semiotics can be defined as the study of signs, including the elements of the signifier and the signified. Roland Barthes stated that the sign system reflects societal assumptions in the context of a particular time and place. In semiotic analysis, there are three main concepts in understanding visual meaning: denotation, connotation, and myth.